Quality of nursing care as perceived by patients and their watchers in selected surgical wards of VLGH-AFP Medical Center - Collado, Estrella P.
Quality care is a right of all patients and the responsibility of all nurses to provide them with (Pearson), 1987. The recipient who is known as the client or patient, is the sole reason for the existence of the hospitals and therefore all services are directed towards his care and rehabilitation. Each patient has the right to receive care in the best ethical manner regardless of the circumstances involving any individual patient, including race, color, sex and social status. The appraisal of the quality of nursing services is an integral part of nursing's responsibility to the public trust. Nursing as a profession must not lose the public's trust. It is imperative to measure and document the quality of care delivered as well as the competence of the nurses. The evaluation of the quality of care rendered requires the formulation of standards for nursing practice. Quality cannot be assessed without standards against which to measure it with the AFP Standards of Nursing Practice devised in 1987 serves as the basis of the type of care rendered by the nurses employed at the V. Luna General AFP Medical Center. It is likewise the tool that documents the structure, process and outcome of practice. Furthermore, these standards are envisioned to ensure operational efficiency and effectiveness in nursing care services. The patient on the other hand, evaluates the quality of nursing care rendered to him. However, with the presence of the family members as watchers, they may influence the patient's perceptions of what quality nursing care constitutes. Since the family is considered the basic foundation in a society, the family should be involved in the planning and implementation of care. The role of the Philippine culture and traditions has been considered extensively when patients are being hospitalized. The conceptual framework of this study was based on the patients' and watchers' evaluation of the services received based on specified nursing behaviors as categorized into the 5 aspects of nursing care, namely: physical care, psychosocial individual, psychosocial group, general care and professional implications. This meant developing a tool on which patients and watchers could state whether or not they have received a certain degree of care and how satisfactory it had been. The quality of care is also influenced by the demographic background and characteristics of patients and watchers. The findings of the study signal nursing service administrators, nursing staff, patients and their watchers to collaborate in determining future health care needs and nurse practice patterns so that the corresponding changes in nursing care at the VLGH-AFP Medical Center can be implemented. Furthermore, the findings serve as practical bases for emphasizing watcher education during in-service training and other continuing education program. Nursing strategies and interventions can be focused on physical care in order to reach the level of patient satisfaction and their watchers. True sentiments and feedbacks regarding their perceptions on the quality of nursing care they receive can lead to the improvement in the service and thus, they will become the prime beneficiaries of a quality nursing care service.